Pengaruh Modifikasi Alat Bola Tenis Terhadap Kemampuan Dasar Tolak Peluru Gaya Ortodoks Siswa Sekolah Menengah Pertama - Dicky Wahyudin; Andrie Chaerul; Ega Trisna Rahayu (Peneliti.net, 2021)
The purpose of making this thesis aims to determine, analyze, and identify the effect of modification of the tennis ball on the basic ability of orthodox style shot put by junior high school students. The author uses a quantitative approach with experimental methods, the form of design in the research design used is a one group pretest posttest design. This research was conducted at SMP IT Nurul Huda Batujaya and the sample in this study were students of class VIII A, totaling 23 students from 47 students of class VIII. There are three stages in this study, namely pretest, treatment or treatment for eight meetings, and posttest. This study was processed using the PASW Statistic 18 application. The results of the study showed that the mean posttest was greater than the mean pretest (45.17>33.30), meaning that the results of the basic ability of orthodox style shot put in class VIII A SMP IT Nurul Huda Batujaya experienced an increase..